FAKTOR-FAKTOR YANG MEMPENGARUHI TRANSPARANSI LAPORAN KEUANGAN PEMERINTAH KOTA - Masruroh, Aviva Fitri; Praptoyo, Sugeng (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2015)
The purpose of this research is to analyze and to test external pressure, uncertain environment, managementcommitment and human resource capacity to the transparency of financial statements. Meanwhile, the samplesin the local government of Mojokerto city and the related government agencies in the local government ofMojokerto city. The data collection technique has been done by issuing questionnaires. The data in this researchis the primary data which has been collected by issuing questionnaires to the respondents. The research methodin this research is quantitative; meanwhile the analysis technique has been done by using multiple linearregression analysis. The result of the research of the determination coefficient value is 75.1%, and each of thevariable i.e. external pressure, uncertain environment, management commitment, and human resource capacityhas significant influence to the transparency of financial statements. Meanwhile, 24.9% of transparency offinancial statements disclosure can be explained by other variables outside the research model. The result ofhypothesis test shows that the influence of external pressure, uncertain environment, management commitmentand human resources capacity variables have positive influence to the transparency of financial statements.Keywords: External Pressure, Uncertain Environment, Management Commitment, Human Resource Capacity,the Transparency of Financial Statements